Enhanced Doppler reflectometry power response: physical optics and 2D full wave modelling. (3rd February 2017) - Pinzón, J R; Happel, T; Blanco, E; Conway, G D; Estrada, T; Stroth, U
Abstract: The power response of a Doppler reflectometer is investigated by means of the physical optics model; a simple model which considers basic scattering processes at the reflection layer. Apart from linear and saturated scattering regimes, non-linear regimes with an enhanced backscattered power are found. The different regimes are characterized and understood based on analytical calculations. The power response is also studied with two-dimensional full wave simulations, where the enhanced backscattered power regimes are also found in qualitative agreement with the physical optics results. The ordinary and extraordinary modes are compared for the same angle of incidence, with the conclusion that the ordinary mode is better suited for Doppler reflectometry turbulence level measurements due to the linearity of its response. The scattering efficiency is studied and a first approximation to describe it is proposed. At the end, the application of the physical optics results to experimental data analysis is discussed. In particular, a formula to assess the linearity of Doppler reflectometry measurements is provided.